An Initiative the Used of Sterile Insect Technique (SIT) To Control Filariasis in Indonesia - Ernawan, Beni; Sasmita, Hadian Iman (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2017)
Filariasis as part of the neglected tropical disease is one of the health problems in the world. Filariasis divided into onchocerciasis (river blindness) and lymphatic filariasis or elephantiasis. This disease caused by filarial nematode parasites Onchocerca volvulus, Wuchereria bancrofti, Brugia malayi and Brugia timori. Filariasis transmitted by several mosquito genera as the vector. Indonesia as endemic filariasis, agreed on plays a role on World Health Organization (WHO) global filariasis elimination in 2020. Sterile insect technique (SIT) is a potential method which can be applied to filariasis elimination program by controlling the mosquito population. Basic principles of SIT involve mass rearing of species target, sterilization process using gamma-rays and releasing sterile male insect into a target area. SIT combined with other methods under one management as Area-wide Integrated Pest Management (AW-IPM) to increasing effectiveness and successful filariasis elimination program in Indonesia. Filariasis elimination program in Indonesia has several challenges and needed public participation to achieve program goals.